Antithrombotic prophylaxis in children and adolescent patients with SARS-CoV-2 (COVID-19) infection: A practical guidance for clinicians - Karimi, Mehran; Bozorgi, Haleh; Zarei, Tahereh; Bordbar, Mohammadreza; Amanati, Ali; Safaei, Arash; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Severe coronavirus disease 2019 (COVID-19) is often associated with features of hypercoagulable state which can manifest as venous thromboembolism (VTE) and/or microthrombosis. Given the high risk of VTE in critically ill COVID-19 patients, appropriate VTE prophylaxis seems to be an important part of managing these patients. Although many protocols regarding venous thromboembolism (VTE) prophylaxis or therapeutic (full-dose) anticoagulation have been conducted worldwide, primarily in hospitalised adult patients, details on paediatric patients, if included, are limited or incomplete. The current evidences suggest that anticoagulation therapy with low molecular weight heparins (LMWH) appears to be associated with better prognosis in patients with moderate to severe COVID-19 induced coagulopathies or elevated D-dimer levels.  Our recommendations are intended to offer guidance for anticoagulation prophylaxis and treatment in COVID-19 children and adolescent patients and not intend to supersede the clinician judgement. We are also conscious that several clinical questions deserve further studies and clarifications because this area is rapidly evolving.